2013
DOI: 10.2139/ssrn.2304450
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation and Stability of Markets

Abstract: Trading skills are highly rewarded in practice but largely ignored in theoretical models of financial markets. This paper demonstrates the importance of skills by examining their interaction with market fragmentation and market stability.We consider a computational model where traders' abilities to accurately price assets are endogenous. In contrast to models that do not consider skills, we find that centralising markets can lead to higher price volatility and less resilience to shocks because it increases the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Ladley et al. ( 2015 ) have shown that centralizing markets can lead to higher price volatility and less resilience to shocks because it increases the equilibrium proportion of unskilled traders. Kovaleva and Iori ( 2015 ) have studied the effects of pre-trade quote transparency on market quality in an artificial limit order market where traders react to the imbalance in demand and supply posted in the limit order book.…”
Section: Agent-based Models and Financial Stabilitymentioning
confidence: 99%
“…Ladley et al. ( 2015 ) have shown that centralizing markets can lead to higher price volatility and less resilience to shocks because it increases the equilibrium proportion of unskilled traders. Kovaleva and Iori ( 2015 ) have studied the effects of pre-trade quote transparency on market quality in an artificial limit order market where traders react to the imbalance in demand and supply posted in the limit order book.…”
Section: Agent-based Models and Financial Stabilitymentioning
confidence: 99%
“…Yeh (2008) uses a genetic programming model to show that greater intelligence improves market efficiency. Ladley et al (2015) use a genetic programming model to investigate the relationship between skill and market fragmentation and show that large numbers of unskilled individuals make the market more susceptible to shocks. Whilst Manahov et al (2014) shows that varying the length of trading strategies impacts trader and market performance.…”
Section: Introductionmentioning
confidence: 99%